The role of imprinting on the adoption of diversity management in German universities. (30th January 2018) - Oertel, Simon
Abstract : This study questions the universal effect of organizational imprinting and argues that the relevance of the imprint differs across organizations' administrative levels. Specifically, this study analyses how institutional founding conditions affect the adoption of diversity management, as a method of responding to increasing institutional pressure to conform to a logic of inclusion and equality in institutions of higher education. Focusing on 112 universities in Germany, results show that the imprint does not affect the adoption of diversity management in general but does so at higher administrative levels. Through a discussion of these findings, this study contributes to a more comprehensive understanding of how imprinting affects organizations. Further, it contributes to a better understanding of factors that influence the diffusion of diversity management in universities.